Chapter 27: Bohr’s Model of Hydrogen Atom - Saifful Kamaluddin, Muzakir (SAP Publications Sdn. Bhd., 2011)
Neils Bohr suggested several important postulates in order to describe the behavior of electron in hydrogen atom. Bohr formulated an equation to estimate the minimum radius of a hydrogen atom can have and the energy level of electron based on their orbit.